50. TWO-WAY EFFECT OF TECHNICAL PROGRESS - Salimov Bakhriddin Lutfullaevich. Bakhriddinov Ulug'bek Bakhriddinovich (Innovative technologies in construction Scientific Journal, 2023)
The article states that there are both positive and negative aspects of industry and technology in the life of man and society, that industry can be both a friend and an enemy of humanity at the same time, based on philosophical laws, humanity and industry are one, based on the law of unity and struggle of opposites. It is analyzed that it develops in a dialectical relationship with one another and that this dialectic relationship is beneficial to humanity on the one hand, and harmful on the other.